2004
DOI: 10.1097/01.ju.0000100110.11129.85
|View full text |Cite
|
Sign up to set email alerts
|

Verotoxin Induces Rapid Elimination of Human Renal Tumor Xenografts in SCID Mice

Abstract: These results suggest that VTs could be candidates for antineoplastic agents against Gb3 expressing tumors for clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 15 publications
2
48
0
Order By: Relevance
“…Shiga toxin as a cytotoxic agent has been tested in xenograft tumor models in mice (11,(22)(23)(24)(25). Furthermore, it eliminates clonogenic tumor cells in purging applications (26).…”
Section: Introductionmentioning
confidence: 99%
“…Shiga toxin as a cytotoxic agent has been tested in xenograft tumor models in mice (11,(22)(23)(24)(25). Furthermore, it eliminates clonogenic tumor cells in purging applications (26).…”
Section: Introductionmentioning
confidence: 99%
“…The B part consists of five identical sub-units, which can all bind to the Gb3 receptor in which the A sub-unit is internalised and cytotoxic through ribosome inactivation (Endo et al, 1988;Olsnes and Sandvig, 1988;Saxena et al, 1989;O'Brien et al, 1992;Gariepy, 2001;Sandvig et al, 2002). VT-1 has shown efficacy against meningioma, astrocytoma, as well as renal tumour xenografts in mice (Arab et al, 1999;Salhia et al, 2002;Ishitoya et al, 2004). The B part of VT-1 has also been suggested as a novel approach to deliver other anti-tumour agents (Vingert et al, 2006).…”
mentioning
confidence: 99%
“…It was shown that intratumoral injection of Shiga toxin inhibits tumor growth. [102][103][104] Another potential application of Shiga toxin is the control of tumor neo-angiogenesis 105 and purging of residual tumor burden from a human B-cell lymphoma xenograft, while sparing normal hematopoietic precursor cells. 106 As a further refinement of the cancer cell targeting approach, it might be suggested to replace the catalytic A-subunit of Shiga toxin by contrast agents for noninvasive tumor imaging or by therapeutic compounds that have preferential effects on cancer cells.…”
Section: Therapeutic Applications Of Toxin Traffickingmentioning
confidence: 99%